Occupational electrical accidents: Assessing the role of personal and safety climate factors. (July 2021) - Baby, Tiju; Madhu, G.; Renjith, V.R.
Highlights: A research survey was conducted in an electrical utility with 3017 responses. Measurement scale for personal safety factors were developed. Hypothesis relating personal and safety climate factors were proposed and significantly validated. Abstract: A research survey is conducted in the large public sector electrical utility in the Kerala state of India. The measurement scale for personal factors like self-esteem, job stress, personal stress, social supports, and fatigue are developed as per the targeted population. Personal safety climate factors of the utility are accessed using existing safety climate scales. 3017 electrical employee's responses from all districts of Kerala state are collected by one to one interaction using the developed instrument. This data is analysed using statistical methods like reliability analysis, confirmatory factor analysis, ANOVA, and explanatory factor analysis. The measurement model shows a good model fit indices, convergent validity, and discriminate validity. Six research hypotheses are validated by statistical analysis. The study found that personal factors, safety climate factors, and health conditions of the workers were significantly correlated to occupational accidents. Personal Attributes - age, job role, education, and experience are significantly effecting the safety behaviour of the electrical workers. All the personal factors significantly correlated with safety climate factors. The results of the study highlighted the need for safety participation, safety knowledge, safety training, and interventions to reduce personal issues in the workplace. These findings provide valuable insights to future researchers to implement novel methods to ensure workplace safety.